2019
DOI: 10.1002/er.4852
|View full text |Cite
|
Sign up to set email alerts
|

Binary mixtures of fatty alcohols and fatty acid esters as novel solid‐liquid phase change materials

Abstract: Summary The discovery of new eutectic phase change materials (PCMs) will overcome the current PCM challenges such as nonbiodegradability, super‐cooling, and limited thermal stability. This paper reports on the development of new bio‐based PCMs composed of binary mixtures of fatty acid esters and fatty alcohols at their eutectic compositions, which provide potential solid‐liquid PCMs for building applications. Six binary systems, namely 1‐dodecanol (DD) + methyl stearate (MES), DD + methyl palmitate (MEP), DD +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…These materials are categorized as inorganic, organic and eutectic (mixture) PCMs. In comparison to inorganic PCMs, organic PCMs (O‐PCMs) possess more desirable properties, such as high LHTES capacity, non‐toxicity, uniform melting, chemically stable, thermally durable, and relatively low volume change during phase change . The O‐PCMs are further classified as fatty acids, parafin, and alcohol in general and inorganic materials are generally salt hydrates .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These materials are categorized as inorganic, organic and eutectic (mixture) PCMs. In comparison to inorganic PCMs, organic PCMs (O‐PCMs) possess more desirable properties, such as high LHTES capacity, non‐toxicity, uniform melting, chemically stable, thermally durable, and relatively low volume change during phase change . The O‐PCMs are further classified as fatty acids, parafin, and alcohol in general and inorganic materials are generally salt hydrates .…”
Section: Introductionmentioning
confidence: 95%
“…In comparison to inorganic PCMs, organic PCMs (O-PCMs) possess more desirable properties, such as high LHTES capacity, nontoxicity, uniform melting, chemically stable, thermally durable, and relatively low volume change during phase change. 2,3 The O-PCMs are further classified as fatty acids, parafin, and alcohol in general and inorganic materials are generally salt hydrates. 4 Cunha and Eames 5 presented a comprehensive review of PCMs between 0 C and 250 C and concluded that the sutable PCMs below 100 C melting temperature are generally organic PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…These are the long-term stability, high phase change enthalpy, and facility of impregnating into porous support material due to their high chemical compatibility and surface tension. The main disadvantage is their high cost [14,18]. Thermal properties of some hydrated salts and eutectic mixtures are presented in Table 4.…”
Section: Eutectic Mixturesmentioning
confidence: 99%
“…Following this, an experimental validation of the predicted values for eutectic mixtures was carried out (Table 3). 34 Phase change properties of the sample derived from biopolymeric material, PHOD, containing preset amounts of 3-HFAs (C8 and C10) has been assessed by DSC showing no clear transition peaks (data not shown). In this case, it can be proposed that the peritectic mixture was formed as in case of certain FAs.…”
Section: Determination Of Eutectic Composition Of Binary Mixtures Omentioning
confidence: 99%
“…16,33 Recently, binary mixtures of fatty alcohols and FA esters with chain length ≥ C12 were derived and suggested to be suitable as PCMs for building application. 34 Phase change properties of the sample derived from biopolymeric material, PHOD, containing preset amounts of 3-HFAs (C8 and C10) has been assessed by DSC showing no clear transition peaks (data not shown). This could be due to the fact that 3-HFAs mixture obtained from this biopolymer was not simple binary mixture but contained at least two other major components, namely unsaturated and saturated C8 and C10 acids in 16% to 25% (w/w) and 4% to 6% (w/w), respectively.…”
Section: Determination Of Eutectic Composition Of Binary Mixtures Omentioning
confidence: 99%